Does Organizational Culture Bridge Corporate Governance and Firm Performance? A Moderated Mediation Conceptual Framework - Gyawali, Bishnu Prasad; Chalise, Mahananda; Sharma, Dilli Raj; Pandey, Pratibha (NPRC Journal of Multidisciplinary Research, 2026)
Background: Prior research in corporate governance has shown that corporate governance has a positive impact on firm performance through various governance mechanisms that help to resolve agency conflicts. However, empirical research has shown that there is no consistent relationship between corporate governance and firm performance, suggesting that corporate governance may be related to firm performance through organizational processes. Objectives: This is a conceptual study that proposes a moderated mediation model to explain how corporate governance is related to firm performance through organizational culture, moderated by institutional pressures. Methods: This study used various theories such as agency theory, stewardship theory, resource-based view, institutional theory, and social capital theory to synthesize various perspectives to propose an integrated model. The integrated model proposes corporate governance as a structural antecedent to organizational culture and organizational culture as an antecedent to firm performance. Institutional pressures are proposed to moderate the relationship between corporate governance and organizational culture. Findings: The integrated model proposes corporate governance to be related to firm performance through organizational culture. Strong corporate governance is likely to result in strong organizational culture through strong leadership behavior and ethical standards. Stronger institutional pressures are likely to result in stronger corporate governance being embedded in organizational culture. Conclusion: The effectiveness of governance is not simply evaluated on the structural provisions; it also depends on the extent to which governance practices become embedded in the organizational culture. The framework accounts for the heterogeneous outcomes of governance on firm performance and provides the theoretical bases for future empirical research. Novelty: This research contributes to the literature in the following ways: (1) it proposes organizational culture as an intervening factor in the governance-firm performance relationship, (2) it expands the resource-based view theory by adding governance as an antecedent of firm-specific intangible cultural resources, and (3) it develops the concept of moderated mediation to describe the indirect effects of institutional pressure on firm performance through organizational culture.